Urban-rural divides in preferences for wetland conservation in Malaysia - Hassan, Suziana; Boye Olsen, Soren; Thorsen, Bo Jellesmark (Elsevier, 2019)
We examined the preferences for wetland conservation among urban and rural dwellers in Malaysia. A choice experiment using face-to-face interviews with urban and rural households was employed. Wetland conservation alternatives were described in terms of environmental protection zones, biodiversity protection, recreational services and flood. Each alternative was connected to a cost for the household, which was a reduction in subsidies for daily goods. Using a latent class model, we identified three groups with distinctly different preferences. The first group comprised mainly rural people with negative willingness to pay for conservation, while the second group included mostly urban people who favored wetland conservation and exhibited positive preference for wetland attributes. The third group was also consisted of mainly urban people who exhibited both negative and positive preferences toward different aspects of conservation. All three groups, however, asserted a strong preference for significant flood risk reduction. The results indicated potential conflicts over wetland conservation impacts and targets. Accordingly, the divide in preferences should be taken into account in policy-making, and the insights provided here may inform efforts to avoid conflict across the population.